OUTSOURCING: DALAM KAJIAN TEORI EKONOMI DAN MANAJERIAL - Nofrivul, Nofrivul (JURIS (Jurnal Ilmiah Syariah), 2014)
Outsoucing was a transfering works and services that were needed by a company to the third party/ vendor (a company which provide services). In comany standing position, it became serial event to get some benefits from retrenchment of human resources. The work link with outsourcing system had caused imbalance position between the employers and the employees. The employers tried to do a trick to this weak people to avoid some obligation (getting licence, applying the decision of worker reduction from company and its compensation and giving reward after getting success in work) which was absolutly being their obligation. These tricks of course would harm these employees in getting their personal right.